International Undergraduates’ Academic Resilience During Onset of the Coronavirus Pandemic’s Educational Disruptions as Evidenced by Term Grade Point Averages - Fass-Holmes, Barry (Journal of International Students, 2022)
How did international undergraduates perform academically during onset of the coronavirus pandemic’s educational disruptions? The present study addressed this question by testing the hypothesis that an American public university’s entire population of international undergraduates who were enrolled throughout academic year 2019–2020 would struggle academically (term grade point averages [GPA] below 2.0) to a greater extent in spring 2020 term (coinciding with the pandemic’s onset) than in fall 2019 and winter 2020 terms (pre-pandemic). Five different analyses of GPAs yielded disconfirmatory, counterintuitive evidence; for example, whereas the hypothesis leads to the prediction that the number and percentage who struggled academically should increase from fall 2019 and winter 2020 terms to spring 2020, the values instead decreased. This report’s results are consistent with these international undergraduates’ resilience and their institution’s beneficial support. Reasons for ruling out alternative explanations (widespread cheating, instructors’ leniency, and grade inflation) are discussed.